Post-Pandemic Textile and Garment Company Resilience in Indonesia - Asep Jamaludin; Citra Savitri; Rengga Madya Pranata; Nandang Nandang; Aji Tuhagana (Yayasan Riset dan Pengembangan Intelektual, 2023)
We test the relationship between firm size, liquidity, leverage, and GDP with financial distress for a sample of companies from IDX Indonesia from 2020 to 2021, using 18 observations of textile and garment companies. In our test, we used panel data regression to test the hypothesis and MRA to measure the moderating variable. We found that almost all textile and garment companies experienced financial difficulties after the pandemic. Firm size and liquidity are factors that affect financial distress in textile and garment companies. Firm size has a positive influence on financial distress. GDP has a positive moderating effect on the relationship between liquidity and financial distress